(untitled) (Oxford, 1996)
Aquaculture engineering requires knowledge of the many general aspects of engineering such as material technology, building design and construction, mechanical engineering and environmental engineering. In this comprehensive book, Odd-Ivar Lekang introduces these principles and demonstrates how such technical knowledge can be applied to aquaculture systems, offering the reader coverage including
Keywords: Aquacultural engineering